2019
DOI: 10.1002/art.40912
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcome of Ustekinumab Therapy for Behçet's Disease

Abstract: Objective. Oral ulcers, the hallmark lesion of Behçet's disease (BD), can be disabling and resistant to conventional treatment, and there is a need for safe and effective treatment. We undertook this study to investigate the long-term safety and efficacy of ustekinumab therapy for BD-related oral ulcers that are resistant to colchicine.Methods. This multicenter, prospective, open-label study included 30 patients who fulfilled the criteria of the International Study Group for BD and who were diagnosed as having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…17 24 Intriguingly, tackling the IL-17 axis with anti-IL-12/23 ustekinumab recently proved effective for the treatment of refractory oral ulcers in BS while also improving joint involvement. 13 In our study, we found evidence supporting the use of secukinumab as an effective and safe therapy for the long-term treatment of active mucosal and articular manifestations of BS.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…17 24 Intriguingly, tackling the IL-17 axis with anti-IL-12/23 ustekinumab recently proved effective for the treatment of refractory oral ulcers in BS while also improving joint involvement. 13 In our study, we found evidence supporting the use of secukinumab as an effective and safe therapy for the long-term treatment of active mucosal and articular manifestations of BS.…”
Section: Discussionsupporting
confidence: 61%
“…6 The phosphodiesterase-4 inhibitor apremilast has been recently approved by the Food and Drug Administration for treatment of oral ulcers, [7][8][9][10] while the interleukin (IL)-1 inhibitors anakinra and canakinumab and the anti-IL-12/23 ustekinumab recently emerged as promising options for refractory oral ulcers in BS. [11][12][13] Articular involvement is common among patients with BS, with a prevalence of 11%-93% depending on the geographical region. 14 Joint involvement is typically a peripheral, non-deforming, non-erosive, asymmetric mono-oligoarthritis of the large and small joints.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing availability of bDMARDs, new targets have been assessed in BS recently. Ustekinumab – a monoclonal antibody targeting interleukin-12 and -23 – was evaluated in a prospective, open-label study, showing promising results in mucocutaneous and articular manifestations resistant to colchicine in BS ( 19 ). In a retrospective study, the anti-interleukin-17 secukinumab was evaluated in the mucocutaneous-articular cluster refractory to initial treatment, revealing itself as a potential alternative in this subgroup ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The second study [16] involved 30 patients, observed for no less than 24 weeks. The authors obtained the results which were similar to the previously described: the mean number of mouth ulcers reduced significantly at the 12 th week of ustekinumab therapy against the initial level (0 vs. 2, р<0.0001).…”
Section: Ustekinumabmentioning
confidence: 99%